Adaptation and validation of the Mexican population type C personality questionnaire (PCTC) - Ceballos Fontes, Marina (Pontificia Universidad Javeriana, 2017)
The aim of this work was the adaptation and validation of the Type-C Personality scale C, by Lopez, Ramirez and Esteve & Anarte (1998, 2002). Linguistic adaptation of the questionnaire was carried out with a sample of 391 people in the cities of Chihuahua and Xalapa, México. Factor analysis led to eliminate six items from the original scale. The remaining items were grouped in four factors. Confirmatory factor analysis indicates that the fundamental factors of type C personality construct are understanding, emotional inexpressiveness, and need for harmony. Nevertheless, need for harmony was not fundamental in the sample from Xalapa. The overall reliability (Cronbach’s alpha) of the scale was 757 and for the four subscales ranged from 0.645 to 0.842.